Optimización en la selección de contribuyentes para la programación de veredictos de la Gerencia Control del Cumplimiento de la Sunat - Reyes Córdova, Reyes Córdova (2021)
The present work of professional sufficiency has as objective to describe my functions performed as operational programmer of the Control and Induction Programming Division of the Lima Intendancy of the Sunat and to demonstrate how the application of information technology affects the automation of the Verdict process, which generates an optimization in the selection of taxpayers allowing that the audit actions may have a greater effectiveness in generating compliance with the tax obligations of taxpayers, enabling this a greater collection and consequently an economic benefit for the country. The report consists of four chapters through which the institutional context of the Tax Administration is described, as well as the problems encountered during the development of the functions are identified, as well as strategies for solving the problems encountered and finally a critical appraisal of the professional training received at the Professional School of Administration is made. For the purposes of the development described above, the descriptive type of research has been used, under the observational method. Finally, based on the information analyzed, it can be concluded that it is necessary to propose modifications to the school's curriculum, such as: inclusion of coaching courses, raising the level of computer courses to intermediate and advanced levels, and creating a job bank that allows greater accessibility to internships and pre-professional internship agreements for students.